Communication and Information Technologies in Social Sciences - Thanh Nguyen, Phong; Safitri, Desy; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang (Opción, 2019)
Methods for applying Communication and information Technology in the learning and teaching of Social Science. Foundation work, for example, ar- ranging, utilizing computer and other mechanical gear in the study hall is talked about. The benefits of utilizing computer, both for the educators and for the understudies are sketched out. Tips on the most proficient method to work with Communication and information Technology just as the imped- iments of Communication and information Technology based learning are clarified in this work.